Detection of Bone Metastases by 68Ga-DOTA-SSAs and 18F-FDG PET/CT: A Two-Center Head-to-Head Study of Gastroenteropancreatic Neuroendocrine Neoplasms. (7th November 2022) - Tian, Rui; Xie, Qing; Yu, Fei; Du, Changzhi; Yao, Xiaochen; Zang, Shiming; Zhang, Chuan; Zhang, Pengjun; Shao, Guoqiang; Yang, Zhi; Wang, Feng; Yu, Jiangyuan
Abstract : Purpose . This study aimed to assess the efficacy of dual-tracer [ 68 Ga-DOTA-somatostatin receptor analogs (SSAs) and 18 F-fluorodeoxyglucose (FDG)] positron emission tomography/computed tomography (PET/CT) imaging for detecting bone metastases (BMs) in patients with gastroenteropancreatic neuroendocrine neoplasms (GEP-NENs). Methods . We retrospectively enrolled 74 GEP-NEN patients with BMs from two centers, who underwent dual-tracer PET/CT from January 2014 to March 2021. We compared and analyzed effectiveness of the dual PET/CT imaging techniques on the BMs, based on 18 F-FDG and 68 Ga-DOTA-SSAs. Specifically, we analyzed the imaging results using χ 2 tests for classification variables, paired-sample tests for number of BMs, Wilcoxon's signed rank test for number of lesions, and the Kruskal–Wallis test for standard uptake value (SUV) ratio comparison. The correlation of dual-tracer SUVmax with Ki-67 index was analyzed by Spearman's correlation coefficient. Results . The detection efficiencies of dual-tracer PET/CT imaging in patients with different pathologies showed discordant for detecting liver metastases and BMs in group neuroendocrine tumor (NET) G3, 68 Ga-DOTA-SSAs was better at detecting BMs for NET G3 (P = 0.049 for SUVT/B and P = 0.026 for the number of metastatic lesions). In addition, statistical significance was found among osteogenesis group, osteolysis group, and the no-change group (for bone SUVT/B value detected by 18 F-FDG and Ki-67 index, osteogenesis group < osteolysis group; for bone SUVT/B detected by 68 Ga-DOTA-SSAs, osteogenesis group > the no-change group). What is more, liver and bone SUVmax and Ki-67 index were positively correlated in 18 F-FDG imaging (P < 0.001 for liver; P = 0.002 for bone), and negatively correlated in 68 Ga-DOTA-SSAs imaging (P < 0.001 for liver; P = 0.039 for bone). Conclusions . 68 Ga-DOTA-SSAs was superior to 18 F-FDG for detecting BMs in NET G1/G2 (well and moderately differentiated NETs), as well as in NET G3 (poorly differentiated NETs). Relatively good differentiation was observed in the osteogenesis group. In addition, dual-tracer PET/CT imaging results were observably correlated with tumor differentiation.